Development of methods for acquiring and transfering measurement data in testing the electric locomotives - Kostić, Dragutin; Drndarević, Vujo; Marković, Petar; Jevtić, Nenad (Transport, 2011)
The paper describes procedures and methods upon which a system has been developed for testing the running behavior of new or reconstructed electric locomotives prior to release them into regular service. Special attention has been paid to precise measurement of traction currents and voltages, as well as non-electrical quantities, such as torque, longitudinal force exerted at the wheel rim, angular and linear velocity, which vary in a wide range. In addition to choosing appropriate sensors and measuring transducers, specific interface circuits were designed and manufactured, and a laboratory model for measuring electrical and non-electrical quantities of traction electric motors was developed and realised. Based on the experience and the results obtained from the laboratory model, a computerised data acquisition system for testing the electric locomotives in the field was designed from such a computerised systems as application program for simultaneous multichannel measurement of mechanical and electrical quantities, and for off-line processing of measurement results. The systems were tested during the operation on measurement and analysis of tractive capabilities, quality of anti slip regulation system, and energy consumption of a modernized locomotive. First Published Online: 09 Jan 2012